Excited States of Xanthene Analogues: Photofragmentation and Calculations by CC2 and Time‐Dependent Density Functional Theory. Issue 19 (30th September 2016) - Kulesza, Alexander Jan; Titov, Evgenii; Daly, Steven; Włodarczyk, Radosław; Megow, Jörg; Saalfrank, Peter; Choi, Chang Min; MacAleese, Luke; Antoine, Rodolphe; Dugourd, Philippe
Abstract: The front cover artwork is provided by the SpectroBio group at the Institut Lumière Matière in Lyon. The image shows the composition of our experimental–theoretical work: a photo of our nanosecond laser setup in the background with the laser‐pulse dependent photofragmentation spectra is the central element. Further elements are the Jacobian matrix for calculating CC2 transition energies, a natural transition orbital, and the energy levels and processes used for constructing the photofragmentation model. Read the full text of the article at10.1002/cphc.201600650 . Abstract : "The nano‐ and picosecond laser‐induced photofragmentation spectra of xanthene analogue dyes are recorded. The photophysics, including the multiphoton absorption of these systems, are analyzed with excited‐state computations. …" This and more about the story behind the front cover can be found in the Full Paper at10.1002/cphc.201600650 .